Illuminating Relationships Between the Pre- and Post-synapse - Sanderson, Thomas M.; Georgiou, John; Collingridge, Graham L. (Frontiers in Neural Circuits, 2020)
Excitatory synapses in the mammalian cortex are highly diverse, both in terms of their structure and function. This is true both at the presynapse, where the probability of neurotransmitter release (P(r)) varies, and also at the post synapse where the complement of neurotransmitter receptors and intracellular proteins are non-uniform. Recently, imaging techniques that allow physiology at the resolution of individual synapses to be investigated have given us greater insight into the relationships between different synaptic properties. One avenue of research relates to the activity level of the synapse, an aspect of which is the P(r). As P(r) is often examined in isolation from postsynaptic properties, the effect it has on the postsynapse is not fully understood. However, it is well established that the pre and post synapse are structurally correlated and compelling evidence indicates that they are also functionally correlated. Further, since postsynaptic receptors at excitatory synapses respond to release of glutamate, it follows that they may be differentially regulated if the frequency of glutamate release is not the same. Indeed, GluA2 containing AMPARs and metabotropic glutamate receptor 1 trafficking has recently been shown to correlate with P(r). In this review we examine how optophysiological tools have been utilized to study the diversity of excitatory synapses in the hippocampus. The role of activity in shaping this variety and the molecular mechanisms that are engaged will be explored. Optical tools together with advanced imaging techniques are ideally suited to probe synaptic diversity further, due to the spatial resolution and control they allow.